2017
DOI: 10.1111/bcpt.12833
|View full text |Cite
|
Sign up to set email alerts
|

Decrease in Oxidative Stress Parameters after Post‐Ischaemic Recombinant Human Erythropoietin Administration in the Hippocampus of Rats Exposed to Focal Cerebral Ischaemia

Abstract: Recombinant human erythropoietin (rhEpo) is a multi-functional drug with antioxidant potential. However, the underlying molecular mechanisms of its action are still unclear. The purpose of this study was to investigate the effects of rhEpo on the brain infarct volume as well as on the levels of the neuronal damage, oxidative stress parameters and active caspase-3, nuclear factor erythroid 2-related factor 2 (Nrf2) and haemeoxygenase-1 (HO-1) expressions in the hippocampi of rats exposed to the right middle cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 81 publications
(112 reference statements)
0
8
0
Order By: Relevance
“…Decreased GPx2 mRNA level in brain tissue may indicate that 1.5 h after hypoxia the level of oxidative stress is reduced by NADA. A reduced levels of ROS and a decrease in GPx activity in rat brains were observed in the recent studies of pre-treatment with metabotropic glutamate receptors agonist (Bratek et al, 2018) and recombinant human erythropoietin (Mršić-Pelčić et al, 2017). The authors suggest that the protective effects of the therapeutic agents determined by the inhibition of ROS production and reduction of oxidative stress.…”
Section: Discussionmentioning
confidence: 86%
“…Decreased GPx2 mRNA level in brain tissue may indicate that 1.5 h after hypoxia the level of oxidative stress is reduced by NADA. A reduced levels of ROS and a decrease in GPx activity in rat brains were observed in the recent studies of pre-treatment with metabotropic glutamate receptors agonist (Bratek et al, 2018) and recombinant human erythropoietin (Mršić-Pelčić et al, 2017). The authors suggest that the protective effects of the therapeutic agents determined by the inhibition of ROS production and reduction of oxidative stress.…”
Section: Discussionmentioning
confidence: 86%
“…Thus, it was shown that MCAO followed by 24 h of reperfusion causes significant neuronal damage in various brain regions. The predominant affected areas are mostly striatum and cortex due to the lack of collateral blood supply (2,18,19). It was described also that immunoreactivity for NeuN decrease significantly following MCAO (20), causing massive corticostriatal lesion with the peak of the damage 12-24 h following reperfusion (20,21).…”
Section: Discussionmentioning
confidence: 99%
“…However, most of the experimental research in various animal models that examined the neuroprotective effects of different doses of rhEpo on brain damage, proposed 5000 IU/kg of rhEpo as optimal dosage (32). It was also shown that rhEpo applied at various time-periods ranging from pre-treatment to up to 24 h after ischemia, exerts the best results when applied within the first 3 h after induction of ischemia (18).…”
Section: Discussionmentioning
confidence: 99%
“…Apparent signs of apoptosis induction were observed in the rat hippocampus one day after MCAO [24]. The death of hippocampal cells via apoptosis was confirmed by the decrease in the expression of anti apop totic protein Bcl 2, as well as by the upregulated expres BIOCHEMISTRY (Moscow) sion of the pro apoptotic protein BAX [25] and the apop tosis executing enzyme caspase 3 in the hippocampus [22,26]. The increase in the number of apoptotic cells was accompanied with pronounced changes in the expression of mRNAs for the NMDA receptor sub units [27].…”
Section: Rapid Responses Of the Hippocampus To The Ischemic Damagementioning
confidence: 91%
“…As established using microdialysis, the extracellular level of glutamate in the rat hippocampus increased within the first minutes of ischemia [21]. The first evidences of the so called delayed death of neurons in this structure were detected later than in the cortex and the striatum [22], as a rule, between 12 h and seven days after the ischemia, with the peak levels on day 4 [23]. Apparent signs of apoptosis induction were observed in the rat hippocampus one day after MCAO [24].…”
Section: Rapid Responses Of the Hippocampus To The Ischemic Damagementioning
confidence: 96%